Madhavi1990 wrote:

Okay, I am a little confused here.

St 1 also boils down to y = -5x

y = x(x^2 -9)

y = x cube - 9x

x cube = 9x + y

Substituting x cube in original equation we get --> y + 9x + y + x = 0 --> 10x + 2y = 0 so y = -5x

and again if I put -5x = x (x^2 - 9) we get x = 2 or -2, inturn making LHS = RHS = 0 [ (-5)(2)]= [2(4-9)]and we get 0 with positive two as well

St 2: y = -5x, same as above. So the LHS = RHS = 0.

Thus, as both statements give 0, Shouldn't the OA be D?

Please request an expert opinion on my answer. Thank you!

\(y + x^3 + x\) is part of the question. You're being asked to find its value, given certain information. Instead, you're treating the problem as if you already know that its value is 0 (by substituting other equations into \(y + x^3 + x = 0\)). This is why it isn't coming out correctly. You're using information that you don't actually have, which will make you get DS problems wrong.

Instead, think to yourself: if the

only information I have is that y = -5x, is that enough for me to figure out the value of \(y + x^3 + x\)? It isn't - you can't figure out what \(y + x^3 + x\) is by using only that information. That's why the statement is insufficient.

_________________